2022
DOI: 10.1002/slct.202201361
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Supported Methionine Selenoxide as an Excellent Immobilized Oxidant for the Formation of Disulfide Bonds in Peptides

Abstract: Two PEG-based polymer supported methionine selenoxide (MeSeO) named TentaGel-MetSeO and PEG-MetSeO were synthesized and used as immobilized oxidants for the purpose of formation of disulfide bonds in peptides under aqueous conditions. Peptide disulfide bonds were successfully synthesized by use of the two immobilized oxidants. Moreover, the oxidation of the methionine residue to its sulfoxide derivate was not observed. By comparison, the yield of disulfidecontaining peptide via PEG-MetSeO oxidation is higher t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Regioselectvie synthesis of two disulfide bonds by the use of the BSA-ODr approach Recently, methionine selenoxide (MetSeO) as an oxidation and deprotecting reagent was used to construct two disulfide bonds in peptides (named SeODR) in a one-pot manner in our laboratories. 18 Inspired by the SeODR reaction, we considered that BSA may also be used to regioselectively construct two disulfide bonds in peptides. Thus, the synthesis of two disulfide bonds in α-conotoxin SI was first investigated by reaction of linear α-conotoxin SI-1 with BSA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Regioselectvie synthesis of two disulfide bonds by the use of the BSA-ODr approach Recently, methionine selenoxide (MetSeO) as an oxidation and deprotecting reagent was used to construct two disulfide bonds in peptides (named SeODR) in a one-pot manner in our laboratories. 18 Inspired by the SeODR reaction, we considered that BSA may also be used to regioselectively construct two disulfide bonds in peptides. Thus, the synthesis of two disulfide bonds in α-conotoxin SI was first investigated by reaction of linear α-conotoxin SI-1 with BSA.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that Br − was a facilitator of the SeODR approach. 18 Thus, the reaction of BSA with oxy (Acm) was also investigated in HBr solution. As expected, oxytocin was successfully generated (entries v-viii).…”
Section: Deprotection Reaction Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these reagents often require long reaction times and/or an excess amount of reagent relative to those of the polypeptides. 13 Thus, the development of techniques to obtain the desired disulfide in high yield and purity remains challenging.…”
Section: Introductionmentioning
confidence: 99%